Use of Single-enzyme PCR-restriction Digestion Barcode Target-ing the Internal Transcribed Spacers (ITS rDNA) to Identify Dermatophyte Species - A Rezaei-Matehkolaei; K Makimura; MR Shidfar; F Zaini; MR Eshraghian; N Jalalizand; S Nouri¬pour-Sisakht; L Hosseinpour; H Mirhendi (Tehran University of Medical Sciences, 2012)
Background: Dermatophytes are the most common causative agents of superficial mycoses. Species identification of these fungi is important from therapeutic and epidemiological point of wive. Traditional approaches for identification of dermatophytes at the species level, relying on macroscopic and microscopic features of the colonies, usually are time-consuming and unreliable in many circumstances. Recently a broad varieties of rapid and accurate DNA-based techniques were successfuly utilized for species delineation of dermatophytes. Methods: The ITS1-5.8S-ITS2 region of rDNA from various reference strains of dermatophyte species were amplified using the universal fungal primers ITS1 and ITS4.The PCR products were digested by a single restriction enzyme, MvaI. The enzyme was evaluated in both in silico and practical PCR-RFLP assay to find the exact differentiating restriction profiles for each species. To validate the standardized PCR-RFLP system, all tested strains were subjected to sequencing and sequence analysis. Results: The obtained RFLP patterns were specific for many species including T. interdigitale, T. rubrum, T. violaceum, M. persicolor, M. audouinii, M. nanum (A. obtusum) and E. floccosum but were similar for some closely related species such as M. canis / M. ferrugineum. Sequencing of the ITS1-5.8S-ITS2 fragment from all type strains affirmed the RFLP findings. Conclusion: It was practically revealed that the ITS-PCR followed by MvaI-RFLP is a useful and reliable  schema for identification and differentiation  of several pathogenic species and can be used for rapid screening of even closely related species of dermatophytes in clinical and epidemiological settings.